The Influence Of Smartphones On The Dynamics Of Social Interaction Among Elementary School Students: A Case Study At Sdk Ruteng I - Maksimilianus Jemali; Sebastianus Catyo Enggong (Yayasan Adra Karima Hubbi, 2026)
Background. This study is motivated by the rampant use of smartphones, which triggers a shift in children's interpersonal relationship patterns. Purpose. It aims to analyze the intensity of smartphone utilization and its impact on the social interaction dynamics of students at SDK Ruteng I. Method. Utilizing a descriptive qualitative approach, data were gathered through observation and in-depth interviews with fifth-grade students. Data validity was verified through source, method, and time triangulation, while data analysis applied the Miles and Huberman interactive model involving data reduction, data display, and conclusion drawing. Results. The findings reveal two primary discoveries: first, students exhibit a high level of smartphone dependency, with daily screen time exceeding two hours; second, smartphones deliver an ambivalent impact, facilitating communication and learning access while simultaneously triggering online game addiction, sleep disturbances, and the loosening of real-world social interactions. Conclusion. As a conclusion, this study highlights that the solution to this phenomenon requires a crucial synergy between parental preventive control through screen time limitation and teachers' persuasive education regarding digital literacy at school.